Proof-of-Concept Application - Annual Report Year 1 - Torsten Eymann; Oscar Ardaiz; Pablo Chacin; Isaac Chao; Juan Carlos Cruellas; Felix Freitag; Manuel Medina; Leandro Navarro; Miguel Valero; Omer Rana; Liviu Joita (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2005)
In this document the Cat-COVITE Application for use in the CATNETS Project is introduced and motivated. Furthermore an introduction to the catallactic middleware and Web Services Agreement (WS-Agreement) concepts is given as a basis for the future work. Requirements for the application of Cat-COVITE with in catallactic systems are analysed. Finally the integration of the Cat-COVITE application and the catallactic middleware is described.
urn:nbn:de:bvb:703-opus-3610
Keywords: 004; Grid Computing